Approaching the Relational Nature of the Port‐City Interface in Europe: Ties and Tensions Between Seaports and the Urban. (30th August 2017) - Hesse, Markus
Abstract: This paper explores the broader setting of urban and economic development that links ports and cities in Europe and aims at enhancing our understanding of the port‐city interface. A relational view is taken for linking local developments and policies with overarching, more remote spheres of influence and impact, which can be considered both beneficial and critical for the port and the city. In order to illustrate the argument, a framework of three issues is applied to discuss the port‐city interface: first, the role of ports as economic engines of their wider region; second, the cruise ship industry as a market segment that re‐connects port and city; third, semi‐political bodies and institutions that play key roles as intermediaries and knowledge brokers. The paper finally discusses the implications of relationality for governing the port‐city interface.